The Relationship between Manufacturing System Performance and Green Practices in Supply Chain Management - Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam; Md Deros, Baba (2011)
Green supply chain management is an increasingly recognized practice among companies that are seeking to improve environmental performance. Of particular concern is how to arouse organizational awareness and put green activities into practice in order to enhance manufacturing performances. This paper investigates the correlation of green supply chain practices and manufacturing performances in Malaysian certified MS ISO 14000 manufacturing firms. The findings shows that green supply chain practices which that can be denominated product recycling,environmental compliance and optimization have significant influence to some of the manufacturing performances.